Chordate evolution and the three-phylum system - Satoh, Noriyuki; Rokhsar, Daniel; Nishikawa, Teruaki (Proceedings of the Royal Society. B, Biological sciences, 2014)
Traditional metazoan phylogeny classifies the Vertebrata as a subphylum of the phylum Chordata, together with two other subphyla, the Urochordata (Tunicata) and the Cephalochordata. The Chordata, together with the phyla Echinodermata and Hemichordata, comprise a major group, the Deuterostomia. Chordates invariably possess a notochord and a dorsal neural tube. Although the origin and evolution of chordates has been studied for more than a century, few authors have intimately discussed taxonomic ranking of the three chordate groups themselves. Accumulating evidence shows that echinoderms and hemichordates form a clade (the Ambulacraria), and that within the Chordata, cephalochordates diverged first, with tunicates and vertebrates forming a sister group. Chordates share tadpole-type larvae containing a notochord and hollow nerve cord, whereas ambulacrarians have dipleurula-type larvae containing a hydrocoel. We propose that an evolutionary occurrence of tadpole-type larvae is fundamental to understanding mechanisms of chordate origin. Protostomes have now been reclassified into two major taxa, the Ecdysozoa and Lophotrochozoa, whose developmental pathways are characterized by ecdysis and trochophore larvae, respectively. Consistent with this classification, the profound dipleurula versus tadpole larval differences merit a category higher than the phylum. Thus, it is recommended that the Ecdysozoa, Lophotrochozoa, Ambulacraria and Chordata be classified at the superphylum level, with the Chordata further subdivided into three phyla, on the basis of their distinctive characteristics.